Upaya Hukum Cessionaris Terhadap Hak Tagih Atas Jaminan Hak Tanggungan Berdasarkan Pengalihan Hutang (Cessie) - Diana Fitriana; Abdul Wahid (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2021)
The sale and purchase and transfer of accounts receivable (Cessie) from the bank to a third party (the new creditor) are by applicable legal provisions, so legally the third party (the new creditor) is the new creditor who has the right to collect on the debtor's obligations based on the credit agreement. However, in reality, since the New Creditor received the transfer of Accounts Receivable on behalf of the debtor, he did not make payments on his obligations based on the credit agreement. The purpose of this research is to find out how the cessionary legal remedies against the right to collect on the guarantee of mortgage based on debt transfer (cessie). The results of this study indicate that the cessionary legal action against the right to collect on collateral based on the transfer of debt (cessie) is filing a lawsuit for default or breaking promises on the credit agreement at the District Court. Cessie buyers must apply to the District Court first so that the District Court's decision can become the basis for the change of name (in its decision, the District Court orders the National Land Agency (BPN) to transfer the name written on the certificate to the name of the cessie buyer.